Art and value : art's economic exceptionalism in classical, neoclassical and Marxist economics - Beech, Dave (Historical materialism book series ;, 2015)
Art and Value is the first comprehensive analysis of art's economics. Key debates in classical, neoclassical and Marxist theories of art are subjected to an exacting critique. The book concludes with a new Marxist theory of art's economic exceptionalism.